Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, dan Penghargaan terhadap Employee Engagement PT Rajawali Hiyoto Malang - Yang Mima Kharisma; Veronika Agustini Srimulyani (JRMA (Jurnal Riset Manajemen dan Akuntansi), 2018)
This study aims to prove empirically the effect of transformational leadership, organizational cultures, and a reward of employee engagement PT Rajawali Hiyoto Malang. Samples in this research is 42 employees of PT Rajawali Hiyoto Malang, the criteria have minimum of high school education or equivalent and a minimum term of 4 years. The results showed that the variables of transformational leadership and organization culture had no effect on employee engagement PT Rajawali Hiyoto Malang, while the variable reward positive significant effect on employee engagement PT Rajawali Hiyoto Malang. The company should maintain a reward system, so that with increasing employee engagement.